ASSOCIATION OF BETA BLOCKER USE AND COPD MORTALITY: A SYSTEMATIC REVIEW - Setyo Irawan, Dwi Wahyu; Chrisdiono, Hermawan (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Chronic obstructive pulmonary disease (COPD) it is currently the third greatest cause of mortality worldwide and one of the main causes of morbidity Aims: This systematic review is to review the association of beta blocker use and COPD mortality. Methods: This study demonstrated compliance with all requirements by means of a comparison with the standards established by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020. Thus, the specialists were able to guarantee that the research was as current as feasible. Publications released between 2014 and 2024 were considered for this search strategy. This was accomplished by utilizing a number of distinct online reference sites, including Pubmed, ScienceDirect, and SagePub. It was determined that reviews, previously published works, and partially completed works would not be included. Result: In the PubMed database, the results of our search brought up 249 articles, whereas the results of our search on SCIENCE DIRECT brought up 18.876 articles, our search on SAGEPUB brought up 4.844 articles. The results of the search conducted for the last year of 2014 yielded a total 131 articles for PubMed, 6.875 articles for SCIENCE DIRECT and 1.840 articles for SAGEPUB. In the end, we compiled a total of 8 papers, 5 of which came from PubMed, 2 of which came from SCIENCE DIRECT and 1 of which came from SAGEPUB. We included eight research that met the criteria. Conclusion: In summary, beta blockers showed the effect to reduce the exacerbation or exacerbation related mortality of COPD in some cases. More studies needed in the future for more evidence of the use of beta blockers as the treatments in patients with COPD.